1983
DOI: 10.1139/b83-297
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of additive "minor-effect" genes for resistance to Puccinia striiformis from Triticum dicoccoides into Triticum durum and Triticum aestivum

Abstract: Transgressive segregation for higher resistance to stripe rust (Puccinia striiformis) was found in segregating populations of crosses of Triticum dicoccoides × Triticum aestivum and T. dicoccoides × Triticum durum. This indicates that additive "minor-effect" gene resistance to stripe rust can be transferred directly from the wild emmer (AABB) to cultivated tetraploid and hexaploid wheats. Since "major-effect" genes for stripe-rust resistance seem to be limited in number, Triticum dicoccoides appears to be a va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…(Miller et al, 1998), stripe rust ( P. striiformis Pers.) (Reinhold et al, 1983), leaf rust ( P. triticina Eriks.) (Dyck and Bartos, 1994), and powdery mildew ( Erysiphe graminis DC.…”
mentioning
confidence: 99%
“…(Miller et al, 1998), stripe rust ( P. striiformis Pers.) (Reinhold et al, 1983), leaf rust ( P. triticina Eriks.) (Dyck and Bartos, 1994), and powdery mildew ( Erysiphe graminis DC.…”
mentioning
confidence: 99%
“…Recently, these wild emmer lines were crossed with two durum wheats and several bread wheats (REINHOLD et al ., 1983) known to possess additive minor-effect genes for stripe rust resistance . Although it has not been proved that these genes in wild emmer do not occur in cultivated wheat, it has been shown that they can act additively when combined either with minor-effect genes or with major-effect genes present in cultivated wheat .…”
Section: Discussionmentioning
confidence: 99%
“…(Miller et al, 1998), resistance to stripe rust ( P. striiformis Pers.) (Reinhold et al, 1983), resistance to FHB (Miller et al, 1998), and grain quality factors (Joppa et al, 1991). A set of disomic chromosome substitution lines from TDIC in the background of Langdon durum had been developed as described by Joppa and Williams (1988) using the TDIC line FA‐15‐3 (“Israel A”).…”
mentioning
confidence: 99%